Electrical transport properties of V2O5 thin films obtained by thermal annealing of layers grown by RF magnetron sputtering at room temperature - Giannetta, Hernan (2015)
The present study investigates the main electrical transport mechanism in V2O5 thin films deposited by RF magnetron sputtering on the basis of the Mott's small polaron hopping model. The material under test was obtained at room temperature from a V2O5 target and then oxidized at high temperature under air atmosphere to obtain the desired V2O5 phase. The dependence of the electrical conductivity of the V2O5 thin films with temperature was analyzed using the Mott's small polarons hopping transport model under the Schnakenberg form. Model results suggest a polaron binding energy WH = 0.1682 eV, with a structural disorder energy WD = 0.2241 eV and an optical phonon frequency ν0 = 0.468 × 1013s- 1. These results are in agreement with data reported in literature for single crystal V2O5. However, the carrier mobility μ = 1.5019 × 10- 5 cm2/Vs computed in the non-adiabatic regime is significantly smaller than that of the single crystal, suggesting a strong electron-phonon coupling in the V2O5 thin films obtained with the proposed deposition method.